Sorting Cilembu Sweet Potatoes Based on Weight Using 2D Image - Setya Permana Sutisna; Tika Hafzara Siregar; Tri Susilo; Alfiani Chairunnisa (Universitas Ibn Khaldun Bogor, 2023)
Cilembu sweet potato is one of the superior products of Cilembu Village, Pamulihan District, Sumedang Regency, West Java Province. Sorting is an important part of post-harvest activities with the aim of separating crops according to certain weight group levels. Grouping based on weight can be done using 2-dimensional (2D) image processing methods. The purpose of this study was to classify Cilembu sweet potatoes based on weight groups using 2D image processing methods. This study uses a 2-dimensional image processing method as an intelligent system in selecting Cilembu sweet potatoes based on size using a sorting tool. The results of the test, the system built can classify Cilembu sweet potatoes by weight with an error value of 6.67%.